Development and characterization of CrN/CrAlN multilayer coatings deposited by hybrid magnetron sputtering process - Castilho, Bruno César Noronha Marques de (2018)
New restrictions and regulations regarding internal combustion engines introduced severe mechanical and thermo-mechanical loads on engine parts, mostly on piston rings, leading to high wear and premature damage, thus causing oil leakage into the combustion chamber and increasing emissions. One of the most viable solutions to overcome these issues is the use of coatings to change surface properties. Coatings produced by High Power Impulse Magnetron Sputtering (HiPIMS) and Direct Current Magnetron Sputtering (dcMS) have shown promising results to form dense coatings with high hardness and high wear resistance. Those properties can be further enhanced by using a periodic structure in the form of multilayers of different materials. In this study, we proposed a hybrid process with HiPIMS and dcMS to produce multilayer coatings of CrN and CrAlN. Different target combinations and negative substrate bias were studied. Furthermore, the base layer influence and an evaluation of the periodicity effects were presented. Structure and morphology of the coatings were characterized with X-Ray Diffraction, Scanning Electron Microscopy and Atomic Force Microscopy. Meanwhile, instrumented nanohardness, corrosion and wear tests were performed to characterize mechanical, electrochemical and tribological properties. Results showed that the choice of target combination and bias values are fundamental for enhancing mechanical and tribological properties. On the other hand, we found no evidence of superlattice hardening when changing periodicity but an increase in corrosion resistance when reducing periodicity was found. The combination of targets, substrate bias, base layer and periodicity presented here showed promising results on wear tests, especially when compared with the current coating under the same engine conditions.